Teachers’ Work Engagement: The Role of Perceived Organizational Support and Meaningful Work - Fridayanti Fridayanti; N. Kardinah; Turi Ati Lestari (Psympathic: Jurnal Ilmiah Psikologi)
This research aimed to determine the effect of perceived organizational support and meaningful work on engagement. The design used was cross-sectional research with the respondents of honorary public 107 Elementary School teachers in Pangandaran Regency. Furthermore, simple random sampling was used and data collection were conducted through three measuring scales, namely Perceived Organizational Support Scale (SPOS), The Work and Meaning Inventory (WAMI), and Utrecht Work Engagement Scale (UWES). Data analysis used multiple linear regression to show the effect of the two variables on work engagement. Therefore, perceived organizational support and meaningful work have a fairly strong role (=.541) in affecting engagement.